Secure and Energy Efficient Distributed Routing protocol using GA-BWO for Large Scale WSNs - Chada Sampath Reddy, Dr. G. Narsimha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Large scale wireless sensor network (LS-WSN)is one of the important parts in modern-day communication that employing low-cost sensor devices with different environmental and physical parameters. The secure communication path between the base station and sensor nodes are built with the help of an efficient routing protocol. In the past years, the existing protocols met few difficulties in terms of higher computational complexity, poor cluster head selection performance, higher energy consumption, lower security, expensive in cluster head selection, scalability management, and uneven load distribution, and so on.In this paper, Secure Energy-Efficient Distributed (SEED) protocol with multiple sink nodes was developed to select the best residual energy. secure path selection using genetic algorithm mutation (GA)with black widow optimization (BWO) approach.The novel routing protocol is named as GA-BWO-SEED. Particularly, the mutation phase of the conventional BWO algorithm is improved with the help of direction average strategy of genetic algorithm. Further, thefuzzy logic system (FLC) selects the most relevant and optima cluster heads. The simulation results shows that the proposed GA-BWO-SEED method demonstrates optimal performance output among all other methods.